The Influence of Leg Muscle Explosive Power and Waist Fitness towards Screen Kick Speed for Pencak Silat Students at PSHT UNDHARI - Chintiya Sari Monica; Dian Estu Prasetyo; Maldin Ahmad Burhan (The Future of Education Journal, 2023)
The background of this research is the low kick speed of the PSHT Pencak Silat athletes from the UNDHARI Commissariat. Efforts to overcome these problems require training Leg Muscle Explosive Power and Waist Flexibility. This study aims to find out whether leg muscle explosive power training and waist flexibility have an effect on the sickle kick speed of PSHT pencak silat athletes. This research is a type of quantitative research using an experimental method approach. While the form of research design used is "one-group pretest-posttest design". The population of this study were all PSHT pencak silat athletes with a total of 10 sons and 10 daughters. The sample of this research is the PSHT PSHT commissariat UNDHARI athletes. The data collection technique used in this study used the leg muscle strength and waist flexibility tests. The data analysis technique used in this research is the normality test and hypothesis testing through SPSS 20 at the level of 0.05. The results of the research show that training on leg muscle explosive power and waist flexibility has a good influence on the results of the sickle kick speed of UNDHARI Commissariat PSHT pencak silat athletes, this can be seen from the pretest and posttest hypothesis test scores obtained from Commissariat PSHT pencak silat athletes. UNDHARI with gains of 0.001 and 0.002 for male athletes and female athletes. Based on the analysis performed, a significant value was obtained from the Explosive Power of the Leg Muscles and Waist Flexibility